Implementasi Peraturan Daerah Surakarta No 12 Tahun 2014 tentang Pencegahan dan Penanggulangan HIV/AIDS - Destania Putri Irawan; Damayanti Suhita; Wirid Winduro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
One of the problems currently being faced is the problem of increasing numbers of people living with HIV/AIDS (Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome). Surakarta Regional Regulation No. 12 of 2014 concerning the Prevention and Management of HIV/AIDS in the City of Surakarta is the first step for the Surakarta City Government to address the problem of the number of new HIV/AIDS cases in the City of Surakarta which are still emerging. The Surakarta City Health Service is the implementing element for government affairs in the health sector. This research aims to describe the implementation of Surakarta City Regional Regulation No. 12 of 2014 concerning the Prevention and Management of HIV/AIDS in the Surakarta City Health Service. In this research, researchers used qualitative descriptive methods. Data collection methods in this research were carried out by means of observation, interviews and documentation. And using Edward III's theory (1980) with indicators of communication, resources, disposition, bureaucratic structure. The results of the research show that the implementation of Surakarta Regional Regulation Number 12 of 2014 concerning the Prevention and Control of HIV/AIDS in the Surakarta City Health Service is seen from four indicators, namely communication indicators have been implemented well and clearly, disposition indicators have been implemented well, bureaucratic structure indicators have been implemented. in accordance with the SOP and resource indicators are quite good but the results of interviews in the facilities section are inadequate. Therefore, it is necessary to improve facilities to facilitate HIV/AIDS prevention and control activities.